2007
DOI: 10.1097/chi.0b013e31814b8eb2
|View full text |Cite
|
Sign up to set email alerts
|

DSM-IV Diagnoses and Obstructive Sleep Apnea in Children Before and 1 Year After Adenotonsillectomy

Abstract: Objectives-Obstructive sleep apnea, a common indication for adenotonsillectomy in children, has been linked to behavioral morbidity. We assessed psychiatric diagnoses in children before and after adenotonsillectomy and examined whether baseline sleep apnea predicted improvement after surgery.Method-Subjects of this prospective cohort study were children aged 5.0-12.9 years-old who had been scheduled for adenotonsillectomy (n = 79), or care for unrelated surgical conditions (n=27, among whom 13 had surgery afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 46 publications
4
52
1
6
Order By: Relevance
“…50 For perspective, the exposure to lead-based paint is associated with an average IQ point loss of less than 4 points. 51 Treatment of SDB has been shown to improve behavior, 39,[52][53][54] attention, 53 quality of life (QOL), 39,55 neurocognitive functioning, 56 enuresis, 57,58 parasomnias (unusual events that occur while asleep), 59 and restless sleep. 60 Even when a clinician strongly suspects SDB exists, some families require objective information to facilitate a clinical decision.…”
Section: Supporting Textmentioning
confidence: 99%
“…50 For perspective, the exposure to lead-based paint is associated with an average IQ point loss of less than 4 points. 51 Treatment of SDB has been shown to improve behavior, 39,[52][53][54] attention, 53 quality of life (QOL), 39,55 neurocognitive functioning, 56 enuresis, 57,58 parasomnias (unusual events that occur while asleep), 59 and restless sleep. 60 Even when a clinician strongly suspects SDB exists, some families require objective information to facilitate a clinical decision.…”
Section: Supporting Textmentioning
confidence: 99%
“…Early case studies reported ADHD symptoms in children referred for evaluation of SDB symptoms (Guilleminault C., 1981). In a study by Dillon et al, of children five to twelve years of age scheduled for adenotonsillectomy, nearly 37% had evidence of ADHD and disruptive behavior disorder (including oppositional and conduct disorder) and about 28% had ADHD (Dillon, 2007). This study also assessed behavioral outcomes after adenotonsillectomy.…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%
“…This study also assessed behavioral outcomes after adenotonsillectomy. Fifty percent of the children who met criteria for ADHD at baseline before adenotonsillectomy no longer did so after surgery (Dillon, 2007). In a review of sixteen studies, parents who reported higher SDB symptoms for their children also reported they had higher inattention and hyperactivity symptoms Cortese, 2009).…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%
“…Moreover, it has been reported that these ADHD-like symptoms are improved with sleep disorder treatment. 18,19 Unfortunately, the findings describing the relationship between ADHD and sleep problems differ depending on the measurement tool used to evaluate sleep problems. For example, studies based on reporting from parents of ADHD patients reveal many sleep problems, but results based on objective measurements have yielded more controversial results.…”
Section: Introductionmentioning
confidence: 99%